Lack of MOF Decreases Susceptibility to Hypoxia and Promotes Multidrug Resistance in Hepatocellular Carcinoma via HIF-1α - Wang, Meng; Liu, Haoyu; Zhang, Xu; Zhao, Wenbo; Lin, Xiaoyan; Zhang, Fei; Li, Danyang; Xu, Chengpeng; Xie, Fei; Wu, Zhen; Yang, Qibing; Li, Xiangzhi (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-inducible factor-1α (HIF-1α) promotes oncogenesis in hepatocellular carcinoma and is functionally linked to cell proliferation, chemoresistance, metastasis and angiogenesis. It has been confirmed that the low expression level of Males absent on the first (MOF) in hepatocellular carcinoma leads to poor prognosis of patients. However, potential regulatory mechanisms of MOF in response to hypoxia remain elusive. Our results demonstrate that MOF expression is negatively associated with HIF-1α expression in hepatocellular carcinoma tissues and in response to chloride-mimicked hypoxia in hepatocellular carcinoma cell lines. MOF regulates HIF-1α mRNA expression and also directly binds to HIF-1α to mediate HIF-1α N-terminal lysine acetylation, ubiquitination and degradation, with downstream effects on MDR1 levels. Functional inactivation of MOF enhances HIF-1α stability and causes cell tolerance to hypoxia that is insensitive to histone deacetylase inhibitor treatment. Dysfunction of MOF in hepatocellular carcinoma cells also results in chemoresistance to trichostatin A, sorafenib and 5-fluorouracil via HIF-1α. Our results suggest that MOF regulates hypoxia tolerance and drug resistance in hepatocellular carcinoma cells by modulating both HIF-1α mRNA expression and N-terminal acetylation of HIF-1α, providing molecular insight into MOF-dependent oncogenic function of hepatocellular carcinoma cells.